2018
DOI: 10.1073/pnas.1803224115
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampus-dependent emergence of spatial sequence coding in retrosplenial cortex

Abstract: SignificanceRetrosplenial cortex (RSC) is a major relay of hippocampal formation output to other neocortical areas and is critical for spatial and some other forms of learning. We show here that the sparse, orthogonal, “place cell” sequence activity in RSC develops gradually over several days and is severely attenuated by hippocampal damage. These data support the theory that hippocampus endows RSC (and possibly other cortical areas) with an index-like, continuous representation of the context in which events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(114 citation statements)
references
References 40 publications
(46 reference statements)
3
102
0
Order By: Relevance
“…RSC spatial responses have been primary examined during track running paradigms (Smith and Mizumori, 2012; Alexander and Nitz, 2015; Alexander and Nitz, 2017; Vedder et al, 2016; Mao et al, 2017; Mao et al, 2018; Miller et al, 2019). Accordingly, we questioned whether there was any relationship between stable firing correlates in free exploration and route running.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RSC spatial responses have been primary examined during track running paradigms (Smith and Mizumori, 2012; Alexander and Nitz, 2015; Alexander and Nitz, 2017; Vedder et al, 2016; Mao et al, 2017; Mao et al, 2018; Miller et al, 2019). Accordingly, we questioned whether there was any relationship between stable firing correlates in free exploration and route running.…”
Section: Resultsmentioning
confidence: 99%
“…Despite possessing dense reciprocal connectivity with numerous regions known to support spatial cognition, few reports have examined spatial response properties of neurons within the RSC. Most assessments of functional properties of RSC neurons have occurred in rodents performing track running tasks (Smith and Mizumori, 2012; Alexander and Nitz, 2015; Alexander and Nitz, 2017; Vedder et al, 2016; Mao et al, 2017; Mao et al, 2018; Miller et al, 2019). Track running experiments have revealed that RSC neurons exhibit spatial correlates with conjunctive sensitivity to allocentric and egocentric coordinate systems (among others) simultaneously (Alexander and Nitz, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This latter mechanism fits well into our conceptualization of systems consolidation; we contend that this is a feature, rather than a side effect, of replay. Although more work is needed for full confidence in this contention -such as experiments that carefully track and manipulate the influence of the hippocampus on cortical representations 15 -we think the evidence already points to replay having a critical and active role in driving consolidation across memory systems.…”
Section: Comparing Integration and Contextual Binding Accounts Of Memmentioning
confidence: 99%
“…Older adults have been found to be 6 slower in learning novel environments and have problems to retrieve this newly learnt information 7 later, even when the results are controlled for their slower learning rate ( the first to be affected during the progression from healthy aging to Alzheimer's disease (AD; Braak & 16 Del Tredici, 2015), the neural mechanisms for age-related deficits in spatial learning are still poorly 17 understood, even in healthy older adults. Studies in rodents and non-human primates showed that 18 place cells in the CA3 subfield of the hippocampus exhibit higher firing rates in aged animals during 19 navigation, and they fail to encode new information when rats encounter novel environments (Thomé,20 Gray O'Mara, 2012). In humans, in contrast, there is evidence for an age-related activity reduction in the 24 hippocampus and medial parietal areas during spatial navigation (Konishi et al, 2013;Moffat, Elkins, 25 & Resnick, 2006).…”
Section: Introductionmentioning
confidence: 99%